Analisis Karakteristik Tanah di Dataran Sikulikap, Sibolangit - Tengku Abdillah Azis; Derita Ramai Durubanua; Regita Asiah Azzarah; Hotdame Martina Sitanggang; Elfayetti Elfayetti (Politeknik Kampar, 2023)
This research explores the soil characteristics in Sikulikap Plain, Sibolangit, North Sumatra, with the aim of assessing its agricultural potential. The plain is known to have Andosol, Alluvial, and Peat soils, collectively creating a fertile environment with high water retention and abundant nutrient availability. The analysis includes parameters such as pH, soil texture, nutrient content, water availability, and soil biological properties. The research results indicate that the soil pH in Sikulikap falls within the range of 6-7, creating optimal acidic conditions for plant growth. The granular soil structure in the A horizon and sandy clay soil texture provide good physical support for agriculture. The biologically rich soil with diverse living organisms adds ecological value to sustainable farming. These findings provide a crucial foundation for sustainable agricultural planning in Sikulikap Plain, with optimal potential for plant growth and increased agricultural production.